Occupational Stress: An Analytical Study of Stress Among Dabbawalas of Mumbai Tiffin Suppliers Association - Menon, Shreekumar; Raithatha, Mehul (Prabandhan: Indian Journal of Management, 2012)
Stress at work is a relatively new phenomenon of modern lifestyles. The nature of work has gone through drastic changes over the last century, and it is still changing at whirlwind speed. They have touched almost all professions, starting from an artist to a surgeon, or a commercial pilot to a sales executive. The paper aims at studying the level of stress among the Tiffin suppliers of Mumbai. It aims at determining the level of satisfaction amongst workers and stress management, analyzing the impact of occupational variables like salary, job timings, and transportation mode, arranged availability/non availability of career advancement measures on the overall job satisfaction. Data has been analyzed by using Correlation and ANOVA test. None of the independent variables are found to be affecting job satisfaction and stress management. The paper concludes that Dabbawalas are satisfied with the current working conditions.